2020
DOI: 10.1177/2059513120932059
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for keloids and hypertrophic scars: a review

Abstract: Purpose: Keloid is a poorly understood disease that is unique to humans. Hypertrophic scars are similar to keloids and may transform into keloids over time. The standard treatments for these scars are limited by inconsistent efficacy and long treatment/follow-up times. Therefore, a new treatment that is effective for all abnormal scar cases is needed. One option may be photodynamic therapy (PDT). This review assesses the current evidence regarding the safety and efficacy of PDT for keloids and hypertrophic sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
(61 reference statements)
0
23
0
Order By: Relevance
“…Consequently, existing scars can be improved by applying fixation tape or gel sheets. It has been formally shown that gel sheets can reduce local skin tension on keloids and hypertrophic scars [4749]. Fixation tape and gel sheets can also promote scar maturation by moderately moisturizing the surface of the scar [33].…”
Section: Main Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, existing scars can be improved by applying fixation tape or gel sheets. It has been formally shown that gel sheets can reduce local skin tension on keloids and hypertrophic scars [4749]. Fixation tape and gel sheets can also promote scar maturation by moderately moisturizing the surface of the scar [33].…”
Section: Main Contextmentioning
confidence: 99%
“…27) Concept Compression therapy has long been used to treat hypertrophic scars that arise from burns [52, 53]. It is also widely used as a conservative treatment for keloids and hypertrophic scars in general [48, 49, 5456]. This therapy is believed to act by placing pressure on the blood vessels in and near the scar.…”
Section: Main Contextmentioning
confidence: 99%
See 3 more Smart Citations